Premoženjskopravni režim javnih zavodov - Bauer, Tanja (Pravnik, 2016)
The issue of the ownership right of public institutions over property used for carrying out their activities is dealt with in this article. The Slovenian Institutes Act adopted in 1991 regulates the field of public institutions with regard to their status. However, many questions remain open. In addition to many other questions, the fundamental question of the ownership of assets of public institutions still remains unclear, in conjunction with Article 65 of the Institutes Act which provides that the property used by a public institution to carry out its activities becomes the property of its founder. In spite of the adoption of the Institutes Act, some public institutions still continue to buy real estate, are still entered into the land register as owners and also they still establish subsidiary companies. Consequently, the question whether, in view of the provisions of the Institutes Act, a public institution can be the owner of this property, became very important. Statutory amendments that will radically alter the organization of public institutions have been in preparation for a long time. They will probably resolve the issue of the property of public institutions. The new act has been publicly discussed many times, however it has not been adopted yet. Notwithstanding, the question is whether such an act will really solve all the problems relating to the assets of public institutions.
Keywords: javni zavodi; lastninska pravica; nepremičnine; pravna ureditev; premoženje